Fetal Brain Transplantation in Kainic Acid Lesioned Caudate Nucleus of Adult Rats - Tandon, P. N. (Hindawi Publishing Corporation, 1992)
This study confirmed that bilateral kainie acid (KA) injection at the caudate produces aphagia and adipsia in rats. The reduction in food and water intake was fatal after a higher dosage of the drug. To test the effect of transplantation on. the mortality, rate, KA was first injected in the left caudate, in one set of rats. After a gap of three days, fetal striatal tissue was unilaterally transplanted at this lesioned site, along with a second injection of KA in the right caudate. Successful transplantation, as ascertained morphologically, did not significantly alter the mortality rate. The morphometric study revealed that the neurons of the transplant were larger in size, and their numerical density lower than those of the caudate of normal rats. Only very few neurons of the transplant developed functional connectivity with the host, as demonstrated by electrophysiological studies.